The association between distal symmetric polyneuropathy in diabetes with all-cause mortality – a meta-analysis - Vági, Orsolya E.; Svébis, Márk M.; Domján, Beatrix A.; Körei, Anna E.; Tesfaye, Solomon; Horváth, Viktor J.; Kempler, Péter; Tabák, Ádám Gy. (Frontiers in Endocrinology, 2023)
Background: Distal symmetric polyneuropathy (DSPN) is a common microvascular complication of both type 1 and 2 diabetes with substantial morbidity burden and reduced quality of life. Its association with mortality is equivocal. Purpose: To describe the association between DSPN and all-cause mortality in people with diabetes and further stratify by the type of diabetes based on a meta-analysis of published observational studies. Data Sources: We searched Medline from inception to May 2021. Study Selection: Original data were collected from case-control and cohort studies that reported on diabetes and DSPN status at baseline and all-cause mortality during follow-up. Data Extraction: was completed by diabetes specialists with clinical experience in neuropathy assessment. Data Synthesis: Data was synthesized using random-effects meta-analysis. The difference between type 1 and 2 diabetes was investigated using meta-regression. Results: A total of 31 cohorts (n=155,934 participants, median 27.4% with DSPN at baseline, all-cause mortality 12.3%) were included. Diabetes patients with DSPN had an almost twofold mortality (HR: 1.96, 95%CI: 1.68-2.27), I2= 91.7%) compared to those without DSPN that was partly explained by baseline risk factors (adjusted HR: 1.60, 95%CI: 1.37-1.87, I2=78.86%). The association was stronger in type 1 compared to type 2 diabetes (HR: 2.22, 95%CI: 1.43-3.45). Findings were robust in sensitivity analyses without significant publication bias. Limitations: Not all papers reported multiple adjusted estimates. The definition of DSPN was heterogeneous. Conclusions: DSPN is associated with an almost twofold risk of death. If this association is causal, targeted therapy for DSPN could improve life expectancy of diabetic patients.